Accessible tourism: the golden key in the future for the specialized travel agencies - Gamze Özogul; Günseli Güçlütürk Baran (Journal of Tourism Futures, 2016)
Purpose – The purpose of this paper is to contribute to the comprehension of the importance of “Accessible Tourism” for the specialized travel agencies by proposing suggestions and key factors to improve the supply of accessible tourism offers. Design/methodology/approach – The paper adopts specialized travel agencies on the accessible tourism perspective of disabled tourist flows. Also, this paper describes the circumstances, social, politic, economic consequences and key decisions that thereby Turkey would be recognized, preferring, establishing on the intention of purchased and suggested positive word of mouth among people. Findings – According to European Commission (EU) (2013) more than half of the individuals with disabilities in the EU made approximately 170 million day trips and a similar number of overnight trips within the EU during the 12 months between mid-2012 and mid-2013. Despite the developments in tourism, lack of product/service appropriate to the travel rights of the individuals with accessibility needs is one of the obstacles should be overcome. Accessible tourism is one of the keys for the survival of the specialized travel agencies in the future. Providing appropriate product/service by targeting the individuals with accessibility needs together with a correct approach and strategy, the specialized travel agencies will be able to have a competitive advantage and continue their activities. Also this market segment will create having sustainable activity and a golden opportunity for the specialized travel agencies in the future. Originality/value – Little research has been done on accessible tourism, future development and on the impact that disabled tourists have on tourism. The paper presents suggestions on what the specialized travel agencies should do with regards to making Turkey be preferred in the future by the individuals having accessibility needs.